The information needs of children having clinical procedures in hospital: Will it hurt? Will I feel scared? What can I do to stay calm?. (18th July 2019) - Bray, Lucy; Appleton, Victoria; Sharpe, Ashley
Abstract: Background: Children often have unmet information needs when attending hospital, and this can cause them anxiety and uncertainty. If children are prepared and informed about what will happen during a procedure, they tend to have a better experience. Finding out what children want to know before they attend hospital for procedures could provide significant benefits for children, their families, and healthcare professionals. This study set out to investigate children's perspectives of what information is important and valuable to know before attending hospital for a planned procedure. Methods: A "write and tell" activity sheet underpinned a semistructured qualitative interview with children attending hospital for a planned procedure. The interview focussed on the information children thought was important to know before a procedure. Data were analysed using content analysis techniques. Results: One hundred six children aged between 8 and 12 years old participated in the interviews. The children identified 616 pieces of information they thought would be of value to children attending hospital for procedures. These were inductively coded into three types of information: procedural, sensory, and self‐regulation. Children want to know detailed procedural and sensory information to actively construct a script of a procedure and then build on this with information about specific strategies to help them cope with and self‐regulate the situation. Conclusion: This study has identified three types of information children recognize as important in preprocedural preparation. Children construct an understanding of a planned procedure through actively scaffolding procedural, sensory, and self‐regulation information.